2011
DOI: 10.1007/s12064-011-0125-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale genetic dynamic modelling I : an algorithm to compute generators

Abstract: We present a new approach or framework to model dynamic regulatory genetic activity. The framework is using a multi-scale analysis based upon generic assumptions on the relative time scales attached to the different transitions of molecular states defining the genetic system. At micro-level such systems are regulated by the interaction of two kinds of molecular players: macro-molecules like DNA or polymerases, and smaller molecules acting as transcription factors. The proposed genetic model then represents the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…6) are based on the principles laid out in Kirkilionis et al (2011). The discrete state spaces S i for the models, i ¼ 1; .…”
Section: Construction Of the Laci Related Submodelsmentioning
confidence: 99%
See 2 more Smart Citations
“…6) are based on the principles laid out in Kirkilionis et al (2011). The discrete state spaces S i for the models, i ¼ 1; .…”
Section: Construction Of the Laci Related Submodelsmentioning
confidence: 99%
“…Compare these definitions with the example model in Kirkilionis et al (2011). With the help of the algorithm described in Kirkilionis et al (2011) we can construct the infinitesimal generators K i , i = 1, 2, 3, 4, 5 for the models I, II, III, IV and V (see Table 1). The corresponding transition graphs are depicted in Fig.…”
Section: Construction Of the Laci Related Submodelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is intended as a general introduction to an approach aimed at studying systems (like a cell) whose processes take place at very different spatial, time and size scales (see [19][20][21]) involving different type of molecular "players". Some relevant applications of this approach can be found in [8][9][10]. The author would like to thank one of the referee for drawing his attention to [2,4,13] where the multiscale analysis is addressed from a more probabilistic point of view.…”
Section: Introductionmentioning
confidence: 99%
“…are of mass-action type, the average dynamics is no longer of that type and usually presents non-linear terms able, for instance, to describe those dynamical features usually termed generically as "nonlinear cooperativity". Novel applications of this approach to the study of synthetic genetic clock can be found in [9,10]; furthermore, the construction of the average dynamics has many features that appears in the modelling of molecular motors, see [1].…”
Section: Introductionmentioning
confidence: 99%